EFEKTIVITAS KURIKULUM BERBASIS MONTESSORI TERHADAP PERKEMBANGAN NUMERASI ANAK USIA DINI - Wanati Wanati; Kartika Fajriani; Lina Revilla Malik (Jurnal Manajemen Pendidikan, 2026)
The purpose of this study is to evaluate the effectiveness of the Montessori method in creating an early childhood education (ECE) program, specifically in improving children's numeracy skills. The background of this study is the low numeracy skills of early childhood children, which are still influenced by the dominance of conventional learning and the limited use of concrete media in the learning process. This study used a quantitative approach with a quasi-experimental design involving an experimental group and a control group. Data were collected through observation, numeracy tests, and documentation. Data analysis was conducted using statistical tests to determine differences in learning outcomes between the two groups. The results showed that Montessori learning significantly improved children's numeracy skills compared to conventional learning. The advantages of this method lie in the use of manipulative media, direct experience-based learning, and a child-centered approach. Furthermore, the Montessori method provides opportunities for children to learn actively, independently, and in a developmentally appropriate manner. This study concludes that the Montessori approach can be used as a strategic alternative in developing an ECE curriculum to improve early childhood numeracy skills.